Integration of Sun and Wind Tracking system Devices Using Arduino - Zain, Anis; Abdullah, M.Faiz Liew (Evolution in Electrical and Electronic Engineering, 2024)
This article explains how to design and build a solar tracking system with Arduino. This method captures free solar energy, stores it in a battery and then converts it into alternating current. As a result, energy can be used as an independent energy source in ordinary homes. The system is designed to respond to its environment in the shortest possible time. Hardware and software issues will be investigated and corrected if necessary. The responsiveness, reliability, stability, and real-time security of our systems have all been tested. The architecture of the system is highlighted, emphasizing resistance to weather, temperature and some minor mechanical influences.